Code-Switching Explorations in Teaching Early Number Sense - Gabriela Arias de Sanchez (Education Sciences, 2018)
New semiotic perspectives about the role of language in mathematics education indicate that teachers have a fundamental role in communicating and teaching the language that carries mathematical meaning. However, little is known about how educators of young children understand and use the language of mathematics. This study addresses this void. Supported by the understanding that mathematics has its own language (Pimm, 1987), the study focuses on code switching—the mixing of words from two languages—by educators as they shift between the language of instruction and the language of mathematics. A qualitative multiple case study approach utilizing discourse analysis was used to explore three early years teachers’ math talk. Findings indicate that these educators code-switched to the mathematics register when they talked about numbers, number words and counting, to revoice students’ ideas, to explain students’ and teachers’ actions, to provide new math information, and when they chose between two terms that belonged to the math register. Findings also demonstrated that educators preferred to avoid the use of the mathematics’ register and relied instead on what the educators called “familiar language.” Findings further indicated the presence of semantic patterns between perceptual terms and the mathematics register.